Causes Of Job Stress Among Sales Professionals- A Study Of A Multinational Subsidiaries In The Asia Pacific Region - Moon, Ho Sze (2009)
This study identifies the causes of the job stress among sales professionals in Oil and gas MNC's subsidiaries in the Asia Pacific region. the sales professionals are supervised under a global management. recommendations to leverage the stress are discussed.